MEDICAL IMAGING APPARATUS INCLUDING BIOLOGICAL SIGNAL PROCESSING SYSTEM, MEDICAL IMAGING SYSTEM, AND BIOLOGICAL SIGNAL PROCESSING METHOD (2021)
The present invention provides a technique capable of accurately and automatically setting a region of interest for acquiring biological information based on a biological information signal obtained from a subject placed in an examination space in a non-contact manner. A signal analyzing unit of a medical imaging apparatus uses the biological information signal for each of a plurality of regions included in a predetermined range among signals measured by a biological information measuring apparatus to select the region of interest in which movement of the subject is to be acquired among the plurality of regions. The movement of the subject is calculated using the biological information signal measured by the biological information measuring apparatus from the selected region of interest.